An 8 Years Retrospective Study of Breast Cancer Incidence in Ilam Province, Western Iran - Yasemi M.; Hafezi Ahmadi M.R.; Khajavikhan J.; Peyman H.; Asadollahi K.H.; Yasemi M.R.; Hemati K. (Journal of Clinical and Diagnostic Research, 2013)
Introduction: Breast cancer is the most common cancer (27% of all cancers) and common cause of death (16%) which occurs due to cancers among women, either in developed or developing countries. The current study aimed to assess incidence of breast cancer in west of Iran (Ilam province). Methods: During a cross-sectional study, all documented records of patients who were referred to the health centre of Ilam province in a period of 8 years (2002-2009) were investigated and 82 files which were related to breast cancer were identified. Patients’ data were entered into SPSS, version 16 and using X2, t-test and descriptive statistics, they were analyzed. Results: Totally, 82 confirmed breast cancer cases were diagnosed between 2002-2009 and this figure accounted for 21.4% of all cancers in Ilam province. The mean age with standard deviation (SD) of patients was 47.4 ± 14.5 years and the disease was most frequent in the age group of 30-40 years (38.3%). The highest incidence rate was seen in 2006- 2007 and the lowest rate was seen in 2002-2003. The most prevalent morphologic pattern of breast caner (86.2%) was invasive ductal carcinoma (IDC). There was a 23% incidence rate for breast cancer, with a significant increase in its incidence rate during 2002-2009. Conclusions: Due to diagnosis of the disease in its advanced stages, and also involvement of low age groups and young population in the country, screening programs such as self examination, examination by doctors and mammography should be started in the lower age groups, in ages which are lower than 30 years.